Thermal and microstructural stability of nanostructured surface of the aluminium alloy 7075 - Pandey V.; Chattopadhyay K.; Srinivas N.C.S.; Singh V. (My University, 2025)
A nanostructured surface layer with average grain size of about 25 nm was developed through ultrasonic shot peening (USSP) on the peak aged and retrogressed aluminium alloy 7075 (AA7075). Thermal stability and other features such as precipitation of hardening particles, grain growth kinetics and microstructural evolution of the nanostructured surface were investigated using XRD and TEM, following annealing at different temperatures from 150 °C to 350 °C. Small peaks of MgZn 2 precipitates were observed in the as USSP treated condition and also after annealing at 150 °C for 30 min. The intensity of these peaks was increased from annealing at 200 °C and the size of precipitates was increased. The nanograins formed from the USSP treatment were thermally stable up to 200 °C, recrystallized at 250 °C and started coarsening at 300 °C, however, the grain size following annealing even at 350 °C was <500 nm. Quantitative evaluation of the different strengthening processes showed that grain boundary strengthening as per the Hall-Petch relationship and dislocation induced hardening based on the Bailey-Hirsch relationship were the dominant mechanisms of strengthening. © 2019 Elsevier Inc.